Village Food-Security Program Implementation in Kendalpecabean: Pelaksanaan Program Ketahanan Pangan Desa di Kendalpecabean - Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2025)
General background: Food security is a national strategic issue and villages are crucial actors for local resilience. Specific background: Kendalpecabean Village started a food-security program in 2022 (post-COVID recovery) using village funds and infrastructure interventions (irrigation, pump houses) to mitigate flood-related crop failures. Knowledge gap: Despite budget allocations and infrastructure works, implementation obstacles remain in training, institutional coordination, and sustainable outcomes. Aims: This study analyzes program implementation using Edward III’s framework (communication, resources, disposition, bureaucratic structure). Results: Qualitative data (interviews, observation, documents) show effective communication and commitment (disposition), concrete infrastructure investments (~Rp 262,000,000 in 2024), but limitations in sustained training and full operationalization of LP2B (land protection) regulations. Novelty: Provides empirically grounded account of a village-level LP2B response combining engineering and institutional measures. Implications: Policy should pair infrastructure investments with capacity-building, clearer LP2B regulation, and institutional support to convert investment into reliable increased yields. Highlights: Village invested ~Rp 262,000,000 (2024) for irrigation and flood-control measures. Edward III framework finds communication and disposition relatively strong; training and LP2B regulation lag. Infrastructure alone limited—continuous capacity building and formal LP2B rules needed. Keywords: Food Security; Village Program; LP2B; Irrigation Infrastructure; Edward III.